If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 + -7x + -5 = 2x + 9 Reorder the terms: 2 + -5 + 3x + -7x = 2x + 9 Combine like terms: 2 + -5 = -3 -3 + 3x + -7x = 2x + 9 Combine like terms: 3x + -7x = -4x -3 + -4x = 2x + 9 Reorder the terms: -3 + -4x = 9 + 2x Solving -3 + -4x = 9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + -4x + -2x = 9 + 2x + -2x Combine like terms: -4x + -2x = -6x -3 + -6x = 9 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + -6x = 9 + 0 -3 + -6x = 9 Add '3' to each side of the equation. -3 + 3 + -6x = 9 + 3 Combine like terms: -3 + 3 = 0 0 + -6x = 9 + 3 -6x = 9 + 3 Combine like terms: 9 + 3 = 12 -6x = 12 Divide each side by '-6'. x = -2 Simplifying x = -2
| 7.72x+16=59.5984+4x | | x^2-5x+19=0 | | 5-5n-4=11 | | r^2=24 | | x+2(5+3x)=87 | | 3x=5-4 | | 3x-5+2x=20 | | 12x+5=4x+3 | | 3x-3-4=5 | | r^2-24=0 | | 46+2x=6x+8x+10 | | 1.35m+0.03=7.80 | | y=100x+400 | | 4(6n-4)=128 | | 2m-5=37 | | 4x+18=6x-2 | | 2a+5(a+3)= | | -8(1-7n)=216 | | 3(7x+8)+6(4x+9)=213 | | 3-4(x+7)=13 | | 6x-10+4x+30=50 | | 2(x-7)+12=24 | | 110=5(-8+6x) | | 4(y+2)=332 | | 3x+5(x-9)=12 | | 8(x-5)=34 | | -8n+2(-5n+3)=-12 | | -8(2+7x)=-240 | | 6(y-2)+4=46 | | 6+29=8x+13 | | -5n-6n= | | (2x+6)(3)= |